Differences in Climbing Ability of Cimex lectularius and Cimex hemipterus (Hemiptera: Cimicidae) - Dae, Yun Kim; Johan, Billen; Stephen , L. Doggett; Chow, Yang Lee (Oxford University Press, 2017)
The climbing abilities of two bed bug species, Cimex lectularius L. and Cimex hemipterus (F.), were determined by evaluating their escape rates from smooth surface pitfall traps using four commercial bed bug monitors (Verifi Bed Bug Detector, ClimbUp Insect Interceptor, BlackOut Bed Bug Detector, and SenSci Volcano Bed Bug Detector). All detectors were used in the absence of lures or attractants. Unlike C. lectularius, adult C. hemipterus were able to escape from all traps. On the other hand, no or a low number nymphs of both species escaped, depending on the evaluated traps. Examination of the vertical friction force of adults of both species revealed a higher vertical friction force in C. hemipterus than in C. lectularius. Scanning electron microscope micrograph observation on the tibial pad of adult bed bugs of C. hemipterus showed the presence of a greater number of tenent hairs on the tibial pad than on that of adult C. lectularius. No tibial pad was found on the fourth and fifth instars of both species. Near the base of the hollow tenent hairs is a glandular epithelium that is better developed in adult C. hemipterus than in adult C. lectularius. This study highlights significant morphological differences between C. lectularius and C. hemipterus, which may have implications in the monitoring and management of bed bug infestations.